Specifying the assessment of translators’ professional competences in the curriculum - Tomash Vrabel; Vrábely Tamás; Врабель Томаш (ДВНЗ “УжНУ”-Поліграфцентр «Ліра», 2020)
Abstract. The article focuses on assessing the professional competences of students majoring in translation and its reflection in the curriculum. Training in translation is, unfortunately, often treated in the same way as teaching a foreign language. The author distinguishes between translation as a professional activity and linguistic (or pedagogical) translation. The latter is only used in the process of studying foreign languages as a way of practising linguistic patterns and constructions. This paper specifies the requirements that translators-to be have to master during their studies. Special attention is paid to the errors caused by poor mastery of translator’s competences. This work describes the skills students have to master to become professional translators. Furthermore, provisional stages of translation are analysed in detail: the pre-translation analysis, the rewording stage, and the post-translation analysis. The author substantiates that even if pre-translation analysis occurs prior to translation, and the post-translation analysis follows it, the activity between these stages is not a linear sequence. Translation is a creative process and elements of one stage can occur at other stages in case a text segment is reinterpreted or needs further analysis / explanation. The mastery of translation can be checked both orally and in written form as a kind of ongoing monitoring and intermediate control. However, the main kind of class activity is written translation done at home and its discussion in the group. It is suggested that knowledge of thematic vocabulary, though obligatory, cannot serve the ground for giving a student a higher mark unlike insufficient or lack of thematic vocabulary knowledge that can lower the mark. The conclusion is drawn that students’ professional skills are to be assessed comprehensively based on the translation of a coherent text.

Резюме. У статті розглядається оцінка професійних компетенцій студентів спеціальності переклад та її відображення у робочій програмі. Методику викладання перекладу, на жаль, часто вважають тотожною викладанню іноземної мови. Автор розрізняє переклад як професійну діяльність та лінгвістичний (або педагогічний) переклад. Останній використовується виключно у процесі вивчення іноземних мов для практики й засвоєння мовних конструкцій. У цій роботі зазначаються вимоги до майбутніх перекладачів, які необхідно засвоїти під час вивчення дисципліни. Спеціальна увага приділяється помилкам, викликаним недостатнім володінням перекладацькими компетенціями. У цьому дослідженні описуються навички, які студенти повинні опанувати для того щоб стати професійними перекладачами. Крім того, детально проаналізовано умовні стадії перекладу: перекладацький аналіз, стадія переформулювання та постперекладацький аналіз. Автор обґрунтовує думку, що навіть якщо перекладацький аналіз відбувається до перекладу, а постперекладацький аналіз після нього, діяльність між цими стадіями не є лінійною послідовністю. Переклад – творчий процес і елементи однієї стадії можуть відбуватися на іншій у випадку якщо сегмент тексту необхідно переосмислити або він потребує подальшого аналізу / пояснення. Володіння навичками перекладу можна перевірити усно й письмово у формі поточного й проміжного контролю. Однак, основним видом аудиторного заняття є письмовий переклад, виконаний вдома та його обговорення у групі. Хоча знання тематичної лексики і є обов’язковим, це не є підставою підвищувати студентам оцінку за переклад. Проте, недостатньо високі знання лексики або їх відсутність може знизити оцінку. Автор доходить висновку, що професійні навички студентів необхідно оцінювати комплексно на підставі перекладу зв’язного тексту.
Keywords: curriculum; professional competences; pedagogical translation; pre-translation analysis; post-translation analysis; intermediate control